Comprehensive Tools of Alkaloid/Volatile Compounds–Metabolomics and DNA Profiles: Bioassay-Role-Guided Differentiation Process of Six Annona sp. Grown in Egypt as Anticancer Therapy - Mona A. Mohammed; Nahla Elzefzafy; Manal F. El-Khadragy; Abdulhakeem Alzahrani; Hany Mohamed Yehia; Piotr Kachlicki (Pharmaceuticals, 2024)
Trees of the Annona species that grow in the tropics and subtropics contain compounds that are highly valuable for pharmacological research and medication development and have anticancer, antioxidant, and migratory properties. Metabolomics was used to functionally characterize natural products and to distinguish differences between varieties. Natural products are therefore bioactive-marked and highly respected in the field of drug innovation. Our study aimed to evaluate the interrelationships among six Annona species. By utilizing six Start Codon Targeted (SCoT) and six Inter Simple Sequence Repeat (ISSR) primers for DNA fingerprinting, we discovered polymorphism percentages of 45.16 and 35.29%, respectively. The comparison of the profiles of 78 distinct volatile oil compounds in six Annona species was accomplished through the utilization of GC-MS-based plant metabolomics. Additionally, the differentiation process of 74 characterized alkaloid compound metabolomics was conducted through a structural analysis using HPLC-ESI-MSn and UPLC-HESI-MS/MS, and antiproliferative activities were assessed on five in vitro cell lines. High-throughput, low-sensitivity LC/MS-based metabolomics has facilitated comprehensive examinations of alterations in secondary metabolites through the utilization of bioassay-guided differentiation processes. This has been accomplished by employing twenty-four extracts derived from six distinct Annona species, which were subjected to in vitro evaluation. The primary objective of this evaluation was to investigate the IC50 profile as well as the antioxidant and migration activities. It should be noted, however, that these investigations were exclusively conducted utilizing the most potent extracts. These extracts were thoroughly examined on both the HepG2 and Caco cell lines to elucidate their potential anticancer effects. In vitro tests on cell cultures showed a significant concentration cytotoxic effect on all cell lines (HepG2, HCT, Caco, Mcf-7, and T47D) treated with six essential oil samples at the exposure time (48 h). Therefore, they showed remarkable antioxidant activity with simultaneous cytotoxic effects. In total, 50% and 80% of the A. muricata extract, the extract with the highest migratory activity, demonstrated a dose-dependent inhibition of migration. It was strong on highly metastatic Caco cells 48 h after treatment and scraping the Caco cell sheet, with the best reduction in the migration of HepG2 cells caused by the 50% A. reticulata extract. Also, the samples showing a significant IC50 value showed a significant effect in stopping metastasis and invasion of various cancer cell lines, making them an interesting topic for further research.